2005
DOI: 10.1364/opex.13.003348
|View full text |Cite
|
Sign up to set email alerts
|

Square spiral 3D photonic bandgap crystals at telecommunications frequencies

Abstract: We present evidence of complete, three-dimensional photonic bandgaps in obliquely deposited thin films with a porous microstructure of tetragonally arranged square spirals. We further present a capability to engineer the bandgap center to wavelengths as low as 1.65 mum, with bandgap widths of up to 10.9%. Using new deposition methods that provide detailed control over the photonic crystal dimensions and morphology, this approach allows advanced photonic crystal architectures to be realized over large scales wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…(b) SEM micrographs of square-spiral Si structures arranged in a tetragonal lattice to form a 3D photonic crystal. This arrangement is obtained by deposition on a substrate with a periodic topography of small seeds, as shown in the right micrograph [506]. and methane at mild temperatures (150°C) [470].…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
“…(b) SEM micrographs of square-spiral Si structures arranged in a tetragonal lattice to form a 3D photonic crystal. This arrangement is obtained by deposition on a substrate with a periodic topography of small seeds, as shown in the right micrograph [506]. and methane at mild temperatures (150°C) [470].…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
“…Mbise et al 14 reported extensively about angular selective transmittance of slanted columnar thin films from different materials with a potential application for window coatings. Rovira et al 15 investigated the phenomenon of optical activity and determined optical rotation of helical structured thin films, and Jensen and Brett 16 reported on reflectance and transmittance of three-dimensional photonic band gap crystals composed of square spirals, for example. Zhang and Zhao 17 theoretically investigated the pitch-height dependent optical extinction spectra of helical Ag nanostructures by the discrete dipole approximation.…”
Section: Introductionmentioning
confidence: 99%
“…3(b) shows an enlarged side view illustrating the intertwining between the adjacent spiral columns which are phase-shifted by an amount equivalent to c/2 (indicated by the yellow and red arrow). Such phase-shifting are straight-forward to implement in laser writing but not possible for other fabrication techniques like the glancing angle deposition [21].…”
Section: Resultsmentioning
confidence: 99%